Prediction of the knock propensity of biogenous fuel gases: Application of the detonation theory to syngas blends. (1st May 2020) - Lechner, R.; Hornung, A.; Brautsch, M.
Abstract: Prediction of the knock propensity is crucial for design and control of engines operating on syngas from thermo-chemical conversion. Classical fuel rating methods such as the methane number or the propane knock index were found to fail for the syngas compositions encountered in practice. A detailed chemical kinetics simulation of the critical compression ratio in an ideal homogenous auto-ignition reactor was tested as an alternative rating method, but was found to also have serious drawbacks and provoke misleading results due to overlying thermodynamic effects. Thus, a novel methodology based on the detonation theory was successfully adopted. The method centres on the two dimensionless parameters ξ and ε which characterise the possible regimes of auto-ignition propagation originating from hot spots. The ξ - ε diagram was applied to a total of 38 fuel blends including reference fuels and syngas compositions determined with a statistical mixture plan supplemented by measured data. The gas measurements were taken at an industrial scale intermediate pyrolysis plant featuring the Thermo-Catalytic Reforming technology of Fraunhofer UMSICHT. Practically all syngas blends showed to be more prone to knock than methane or biogas, albeit not more than propane, which is a standard fuel used in gas engines. Admixtures of higher hydrocarbons were found to substantially increase the knock propensity. Lean equivalence ratios, exhaust gas recirculation and the addition of water vapour were effective measures to mitigate the risk of knock. The anti-knock effect of dilution could be primarily attributed to a reduction of the amount of energy transferred into the acoustic front of an auto-ignition wave.